2022
DOI: 10.3390/catal12060579
|View full text |Cite
|
Sign up to set email alerts
|

Protein Engineering of Pasteurella multocida α2,3-Sialyltransferase with Reduced α2,3-Sialidase Activity and Application in Synthesis of 3′-Sialyllactose

Abstract: Sialyltransferases are key enzymes for the production of sialosides. The versatility of Pasteurella multocida α2,3-sialyltransferase 1 (PmST1) causes difficulties in the efficient synthesis of α2,3-linked sialylatetd compounds, especial its α2,3-sialidase activity. In the current study, the α2,3-sialidase activity of PmST1 was further reduced by rational design-based protein engineering. Three double mutants PMG1 (M144D/R313Y), PMG2 (M144D/R313H) and PMG3 (M144D/R313N) were designed and constructed using M144D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The oligosaccharide content change caused by adding sugar during processing has not yet been explained. From this study, it was speculated that monocrystal rock sugar (used in this study) could be hydrolyzed into glucose and fructose [ 28 , 29 , 30 , 31 ], in which the glucose could be dehydrated and condensed with galactose sialate by heat treatment to form 3′-sialyllactose. In sum, it showed that adding sugar (monocrystal rock sugar) could increase the nutritional value of edible bird’s nest products within the tested range.…”
Section: Resultsmentioning
confidence: 99%
“…The oligosaccharide content change caused by adding sugar during processing has not yet been explained. From this study, it was speculated that monocrystal rock sugar (used in this study) could be hydrolyzed into glucose and fructose [ 28 , 29 , 30 , 31 ], in which the glucose could be dehydrated and condensed with galactose sialate by heat treatment to form 3′-sialyllactose. In sum, it showed that adding sugar (monocrystal rock sugar) could increase the nutritional value of edible bird’s nest products within the tested range.…”
Section: Resultsmentioning
confidence: 99%